DRAINAGE CO-EFFICIENT FOR MOLE DRAINS TO RECLAIM DEGRADED VERTISOLS OF GODAVARI BASIN - A. SAMBAIAH*, M. RAGHU BABU, G. RAVI BABU, G.V. LAKSHMI and S.B.S. NARASIMHA RAO (The Journal of Research ANGRAU, 2020)
Determination of drainage co-efficient for mole drains for Kapileswarapurammandal, East Godavari districtof Andhra Pradesh was carried out by considering 26-Years daily maximum rainfall events, normal dailyrainfall, Weibul's (5-Year Return Period) rainfall event, cumulative 10-day to 1-day maximum rainfall value, bestfitting distribution (5-Year Return Period) value. Among all, Weibul's (5-Year Return Period) rainfall event andbest fitting distribution (5-Year Return period) rainfall are close to each other and hence, the observed 1-daymaximumrainfall event, which is also arrived using Weibul's method i.e. 157.0 mm of 1-day maximum eventwas considered for estimation of corresponding direct runoff. An event of 157.0 mm rainfall has potential fordamaging the surface layers of the vertisols by ponding and subsurface layers by waterlogging. To evacuateboth surface and subsurface matrix for avoiding the land degradation, effective drainage systems are to bedesigned and made functional. To do so, the direct runoff was estimated using SCS-CN method which is foundto be 101.4 mm needs to be drained. The difference between the 1-day maximum rainfall event and the directsurface runoff (101.4 mm) is the abstraction amount available for preferential flow into the mole drains, i.e.55.6mm d-1. This becomes the drainage co-efficient requirement for the mole drains of the study area, which canbe used in Hooghoudt's equation to arrive at the mole drain spacing. In this study, mathematical models weredeveloped for estimation of mole drain co-efficient (M.D.C.) for the study area and found that the it relates to 1-day maximum with 2nd order polynomial equation with co-efficient of determination of 0.9911 and it relates toreturn period with logarithmic equation with co-efficient of determination of 0.9869.